Enhancing Tunnel Construction Efficiency in Nepal: Assessing Factors and Challenges - Bajgain, Shyam; Rawat, Bikram; Pokharel, Prabhu Ram (Journal of Engineering Issues and Solutions, 2025)
Nepal, situated amidst the Himalayas and bordered by China and India, faces significant challenges in economic development due to rapid urbanization and population growth. With its diverse topography, ranging from low-lying plains to towering peaks, the country’s major economic resources, including water, agriculture, and tourism, necessitates infrastructural development. Tunnels play a crucial role in harnessing these resources, yet Nepal has historically relied on traditional drill-and-blast methods, hindering progress due to limited expertise and financial constraints.This study examines the major challenges associated with drill-and-blast tunneling in Nepal, focusing on factors influencing over-break phenomena. Through a comprehensive analysis of existing literature and primary data collection from selected hydro-power projects, the research identifies key challenges such as army management, tunnel geology, and construction equipment limitations. Moreover, it investigates factors contributing to over-break, including powder factor, blasting pattern, and geological conditions.The study highlights the need for optimized army management, local procurement of construction materials, and diversification of explosive suppliers to enhance efficiency and resilience in tunnel construction projects. Ultimately, this research contributes valuable insights to optimize tunnel construction methodologies and mitigate challenges, thereby fostering sustainable infrastructure development in the region.